2005
DOI: 10.1007/s10461-005-9049-3
|View full text |Cite
|
Sign up to set email alerts
|

HIV, HBV, and HCV Infections Among Drug-Involved, Inner-City, Street Sex Workers in Miami, Florida

Abstract: This study describes the rates of HIV, HBV, and HCV seropositivity among drug-involved, female street sex workers in low-income, inner-city sections of Miami, Florida; further, their sociodemographic characteristics, drug use, and sexual risk behaviors were assessed; and predictors of infection were reported. A sample of 586 sex workers was recruited through targeted sampling methods, interviewed, and counseled and tested for the presence of antibody to HIV, HBV, and HCV. Respondents' median age was 38 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 46 publications
5
37
1
3
Order By: Relevance
“…The factors related to these rates were unsafe sexual practice, homeless condition and drug abuse, among other things. 7 Concerning syphilis, the data found in the present study are comparable to those indicated in the city of Rio de Janeiro, with a prevalence of 5.3% among pregnant women. * Nonetheless, it must be taken into consideration the fact that, in the present study, the treponemic test was carried out only in the VDRL positive cases, underestimating the number of cases referring to serological scars.…”
Section: Discussionsupporting
confidence: 82%
“…The factors related to these rates were unsafe sexual practice, homeless condition and drug abuse, among other things. 7 Concerning syphilis, the data found in the present study are comparable to those indicated in the city of Rio de Janeiro, with a prevalence of 5.3% among pregnant women. * Nonetheless, it must be taken into consideration the fact that, in the present study, the treponemic test was carried out only in the VDRL positive cases, underestimating the number of cases referring to serological scars.…”
Section: Discussionsupporting
confidence: 82%
“…Unsafe vaginal sex increases the risk of acquiring HBV. While becoming infected sexually for HCV is less likely than that for HBV [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that discuss specific groups, such as those who attend clinics for sexually transmitted diseases like drug abusers, homosexuals and sex workers, reveal findings that differ from those of the general population, and the risks of sexual transmission of HCV increase considerably 12,15,18,23,25,26,37,51,61,65,68,69,83,85,91 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of studies mention rates of between zero and 3%. These low indexes, associated with rare risk factors, suggest that sexual transmission presents a minimal or negligible risk 18,30,31,44,49,51,54,69,82,83,92 .Studies that discuss specific groups, such as those who attend clinics for sexually transmitted diseases like drug abusers, homosexuals and sex workers, reveal findings that differ from those of the general population, and the risks of sexual transmission of HCV increase considerably 12,15,18,23,25,26,37,51,61,65,68,69,83,85,91 . …”
mentioning
confidence: 99%